The determinants of learner satisfaction with the online video presentation method. Issue 1 (31st August 2020) - Al Natour, Sameh; Woo, Carson
Abstract : Purpose: The purpose of this paper is to examine the determinants of learners' satisfaction with a new blended learning method, namely online video presentations. Design/methodology/approach: The study tests the proposed model using responses from 353 students who were exposed to the new method. Regression analysis was used to test the hypotheses. Findings: The results show that both the perceived social (e.g. reduction in comparison bias) and utilitarian (e.g. presentation originality) benefits increase satisfaction with the online video presentation method, from both the creator's and the learner's perspectives. Practical implications: This study provides several guidelines to instructors employing blended learning methods, as well as designers of platforms that enable blended learning. Originality/value: This study provides a model to understand the determinants of learners' satisfaction with a new blended learning method. It looks at these determinants from both the content creators' perspective and the content viewer's perspective.